Development and Optimization of Intravaginal Mucoadhesive Microspheres of Econazole Nitrate - Paswan, Suresh Kumar (Asian Journal of Pharmaceutics (AJP), 2023)
The most common disease in the female vaginal tract is vaginal candidiasis caused by the microbe Candida Albicans. The conventional formulation for the treatment of this disease shows a lack of retention of the dosage form in the vaginal cavity due to the natural draining of vaginal fluid that leads to leakiness and Messiness, which tends to escape during normal routine work. The mucoadhesive delivery of antifungal drugs in the treatment of vaginal candidiasis is an alternative to delivering drugs for a longer time. In this research work, econazole nitrate-loaded mucoadhesive microspheres were developed by spray drying method and compressed into a vaginal tablet which disintegrates rapidly into microspheres in the vaginal cavity and adheres to vaginal mucosa for a longer time. Methods and Materials: Econazole nitrate-loaded microspheres were prepared and characterized in terms of particle size, drug loading, ex vivo mucoadhesion study, and in vitro drug release study. A three-factor and three-level Box–Behnken design was employed to optimize the formulation, and the effect of independent variables HPMC K 100M, Eudragit RSPO, and Eudragit RLPO on formulation was analyzed. Results and Discussion: The particle size of the optimized formulation was found to be 25μ. The drug loading and in vitro release study at 6 h were 23% and 93%, respectively. The data from the in vitro drug release study show that the drug is released in a sustained manner due to release retarding polymer Eudragit RSPO and Eudragit RLPO and the % mucoadhesion of the optimized microsphere was found to be 70 % after 8 h in contact with vaginal fluid due to mucoadhesive property of HPMC K100M, tablet disintegrate rapidly into microsphere which adheres to the vaginal wall and consistently release drug up to 6 h. Conclusion: The mucoadhesive microsphere prepared by the spray dryer provides a mucoadhesion phenomenon that allows the adherence of the microsphere to the vaginal mucosa so that drug retention time is increased. The prepared vaginal tablet overcomes the drawback of conventional formulations and disintegrates rapidly into a mucoadhesive microsphere and adheres to the vaginal lumen so that the retention time of the drug is increased.